Monastische Kultur als transkonfessionelles Phänomen: Beiträge einer deutsch-russischen interdisziplinären Tagung in Vladimir und Suzdal’ - Steindorff, Ludwig; Auge, Oliver; Doronin, Andrej Vladimirovič (Veröffentlichungen des Deutschen Historischen Instituts Moskau, 2016)
A comparison between Western European Catholic monasteries and Russian Orthodox monasteries during the late Middle Ages and Early Modern period reveals their common roots in the Western and Eastern monastic traditions as well as similarities in the meaning and practical implementation of their shared early Christian heritage. The adopted social-historical perspective illustrates how the world of the monastery is connected to secular spaces. Ludwig Steindorff/Oliver Auge, Christian-Albrechts-Universität zuKiel